2015 2nd International Conference on Electronics and Communication Systems (ICECS) 2015
DOI: 10.1109/ecs.2015.7124982
|View full text |Cite
|
Sign up to set email alerts
|

ECG signal compression algorithm based on joint-multiresolution analysis (J-MRA)

Abstract: This paper explores the new algorithm for ECG signal compression based on Joint-multiresolution analysis (J-MRA) using Gaussian pyramid and wavelet analysis. From signal compression prospective, MRA play key role to present signal in few numbers of coefficients with its parental features. The proposed algorithm has been tested on 10 second length of 19 ECG signals from MIT-BIH Arrhythmia database and compared with recent contemporary techniques. The simulation results show that the proposed method achieves hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Banerjee et al (2012) used the discrete wavelet transform to clear out noise of ECG signals and detect R-peaks by adapting the multiresolution approach. Kumar et al (2015) explored a method for ECG signal compression based on multiresolution analysis. The results showed that the proposed method achieves a high compression ratio at relatively low distortion.…”
Section: Biomedical Application Of Multiresolution Analysismentioning
confidence: 99%
“…Banerjee et al (2012) used the discrete wavelet transform to clear out noise of ECG signals and detect R-peaks by adapting the multiresolution approach. Kumar et al (2015) explored a method for ECG signal compression based on multiresolution analysis. The results showed that the proposed method achieves a high compression ratio at relatively low distortion.…”
Section: Biomedical Application Of Multiresolution Analysismentioning
confidence: 99%
“…No trabalho de Kumar [47], para a decomposição se utiliza uma análise multi-resolução (MRA) usando uma pirâmide gaussiana, e ao resultado dessa decomposição é aplicada uma DWT. Se realiza uma limiarização do resultado e por última se usa RLE.…”
Section: Métodos Existentes De Compressão De Ecgunclassified